Prevalence of Hand Hygiene and Its Risk to Hand Eczema: A Meta-Analysis - Lely Tri Pangesti; Bhisma Murti; Burhannudin Ischan (Journal of Epidemiology and Public Health, 2023)
Background: Hand eczema is an inflammation of the skin that is limited to the hands and/or wrists. Since the pandemic began, washing hands is one of the actions that can be taken as an effort to prevent the spread of COVID-19. With the increasing frequency of hand washing by health workers during the pandemic, it is important to evaluate the risk of developing hand eczema in health personnel.Subjects and Method: Meta-analysis was carried out according to the PRISMA flow chart and the PICO model (Population: health workers, Intervention: high frequency of hand washing, Comparison: low frequency of hand washing, Outcome: Hand eczema). The databases used are Google Scholar, PubMed, Scopus, Proquest, and Science Direct. Keywords used (hand hygiene) OR (frequency hand washing) AND (hand eczema). There were 17 cross-sectional studies published in 2018 to 2022 that met the inclusion criteria. Analysis was performed with Revman 5.3. Results: A meta-analysis was performed on 17 cross-sectional studies from China, Turkey, India, Thailand, Denmark, Sweden, Bulgaria and Ethiopia. The total sample size is 31,154. A meta-analysis of 10 cross-sectional studies concluded that hand hygiene with a frequency of 8 to 10 times per day has a 1.46 times the risk of having hand eczema compared to hand hygiene with a frequency of <8 times per day (aOR=1.46; 95% CI 1.46 to 1.80; p<0.001). A meta-analysis of 10 cross-sectional studies concluded that hand hygiene with a frequency of 15 to 20 times per day has a 1.58 times the risk of experiencing hand hygiene compared to a frequency of <15 times per day (aOR=1.58; 95% CI 1.43 to 1.74; p<0.001).Conclusion: The higher the frequency of hand hygiene, the higher the risk of hand eczema. Keywords: hand hygiene, risk of hand eczema, health personnel Correspondence:Lely Tri Pangesti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Jawa Tengah. Email: lellytrip@gmail.com. Telepon: 082223360202.